Grundtvigs økonomiske tænkning - Våhlin, Vagn (Grundtvig-studier, 1989)
Grundtvig’s View of Economy By Vagn Wåhlin. Because of his impressive impact on Danish culture and society, Grundtvig has been studied from nearly all angles except that of economic philosophy. Due to his consistent omission of references in his writings about society, it is quite difficult to pinpoint exactly from where and when he got the economic ideas he transformed over the years - especially 1830-1848/49 - into a more total economic understanding and which he in 1848 formulated to an economic program for Danish society at the time of the debate and decision on the Danish democratic Constitution of 1849. The author demonstrates that Grundtvig was well acquainted with the major trends in late mercantilistic, French physiocratic and German cameralistic economic thinking of the late Enlightenment as well as with the mainstream of British (Smith, Ricardo, Malthus, Mill, etc.) and Continental (Saint Simon, Sismondi et al.) economic thinking of his day. He held some of the physiocratic (i.e., predominance to the agrarian sector) and some of the cameralistic (a strong state, the king, balancing social and economic contradicting forces) views. But at the same time, he was strongly in favour of British liberal economics in the world of trade and distribution and against any economic and professional monopolies. Grundtvig’s economic thinking was well in accordance with the social and economic realities and possibilities in the Danish society of around 1850. His economic platform was built on the existing natural (agrarian) resources and traditions (75% of all land under cultivation belonged to the family farms of 20-120 acres). He wanted to learn from the best of foreign experiences and avoid the misfortunes of industrial capitalism: the class wars and the dehumanization of the industrial working force. Believing that labour - manual and intellectual – was the sole source of social wealth, he would favour the solid and hardworking middle strata of farmers on their family farms and the independent craftsmen as the backbone of production and economy. For him, real democracy required not only the right institutions but even more: well educated and economically independent citizens who were aware not only of their political, but also of their moral (Christian) responsibilities to their fellow men in a society where (as he wrote in 1820 and repeated in 1848) Few have too much and Fewer have too little”.